DYNAMICS OF UTILIZING DIGITAL STORYTELLING IN CULTURAL VALUE-BASED COFFEE SHOP MARKETING COMMUNICATIONS - husriadiadi adi (Laboratorium Riset Ekonomi, 2026)
This study examines the dynamics of the use of digital storytelling in coffee marketing communications . A shop based on cultural values, amidst the rapid growth of creative MSMEs and the dominance of social media platforms that demand more emotional and authentic narratives. The purpose of this study is to analyze the process of digital narrative formation, the role of local communities, and adaptation to technological changes and trends, to understand how cultural values are integrated into marketing communication practices. The study used a qualitative approach with a phenomenological design, conducted at coffee MSME shops in Kendari City, with the subjects being owners, workers, content creators, and regular customers. The results show that digital storytelling functions as a narrative bridge between cultural identity, customer experience, and loyalty building, while active involvement of local communities and adaptation of content formats to algorithms increase engagement and brand awareness. Authenticity . The implications of the research emphasize the importance of a narrative-cultural framework in MSME digital marketing strategies, as well as the need for community engagement and ethical regulation of digital content.